2021
DOI: 10.3390/ijerph18073561
|View full text |Cite
|
Sign up to set email alerts
|

The Comparisons of Physical Functional Performances between Older Adults with and without Regular Physical Activity in Two Different Living Settings

Abstract: We compared the physical function performances of community-dwelling and day care center older adults with and without regular physical activity (PA). A total of 163 Taiwanese older adults living in rural communities participated. PA habits and physical functional performances were assessed. The participants were divided into community-dwelling (CD) and senior day care (DC) center groups that were further classified into regular physical activity (RPA) and non-physical activity (NPA) subgroups. Comparison took… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Physical activity has been known to have a positive impact on muscle strength and balance ability, both of which are related to gait speed. 15 , 16 ) Therefore, we expected the patients with active hobbies to have better physical function before their hospital admission, and consequently they might have maintained a fast gait speed even after admission. However, there are reports of patients who exhibited hospitalization-associated disability in which their ADLs were decreased after their hospitalization, and it was estimated that this occurs in about 7.5% of patients with a history of heart failure of 20 years or more and in 30%–40% of elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity has been known to have a positive impact on muscle strength and balance ability, both of which are related to gait speed. 15 , 16 ) Therefore, we expected the patients with active hobbies to have better physical function before their hospital admission, and consequently they might have maintained a fast gait speed even after admission. However, there are reports of patients who exhibited hospitalization-associated disability in which their ADLs were decreased after their hospitalization, and it was estimated that this occurs in about 7.5% of patients with a history of heart failure of 20 years or more and in 30%–40% of elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…In older adults who engage in a composite implementation of the three activities defined in this study, the risks of physical pre-frailty and frailty were found to be low. Cheng et al reported that in 163 community residents, upper-extremity muscle strength, flexibility, and chair-rise speed were cross-sectionally significantly higher in the residents who engaged in regular physical activity compared to those who were inactive [ 31 ]. Other studies of community-dwelling older adults demonstrated that a walking intervention improved depressive symptoms and that exercise increased the subjects’ insulin-like growth factor (IGF)-1 level and reduced inflammation [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The health benefits of physical activity have been widely recognized ( Cheng et al, 2021 ). Proper physical activity can improve muscle, heart, and lung function and reduce the risk of high blood pressure, coronary heart disease, stroke, diabetes, cancer, depression, sleep disorders, falls, and fracture ( de Labra et al, 2015 ; Dipietro et al, 2019 ; Mugueta-Aguinaga and Garcia-Zapirain, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has found that physical activity may be the most effective intervention for frailty ( Cheng et al, 2021 ). It is much more accomplished and effective when performed under supervision ( Bonnefoy et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%